Applications of green technologies‐based approaches for food safety enhancement: A comprehensive review. Issue 9 (28th May 2022) - Islam, Fakhar; Saeed, Farhan; Afzaal, Muhammad; Ahmad, Aftab; Hussain, Muzzamal; Khalid, Muhammad Armghan; Saewan, Shamaail A.; Khashroum, Ashraf O.
Abstract: Food is the basic necessity for life that always motivated man for its preservation and making it available for an extended period. Food scientists always tried to preserve it with minimum deterioration in quality by employing and investigating innovative preservation techniques. The food sector always remained in search of eco‐friendly and sustainable solutions to tackle food safety challenges. Green technologies (ozone, pulsed electric field, ohmic heating, photosensitization, ultraviolet radiations, high‐pressure processing, ultrasonic, nanotechnology) are in high demand owing to their eco‐friendly, rapid, efficient, and effective nature in controlling microbes with a negligible residual impact on food quality during processing. The use of green technologies would be a desirable substitute for conventionally available preservation techniques. This paper discusses different food preservation techniques with special reference to green technologies to minimize the deleterious impact on the environment and employs these innovative technologies to play role in enhancing the food safety. Abstract : The current review article discusses different food preservation techniques with special reference to green technologies to minimize the deleterious impact on the environment and employs these innovative technologies to play role in enhancing the food safety.